1993
DOI: 10.1093/rheumatology/32.7.595
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Year, Placebo-Controlled Trial of Non-Steroidal Anti-Inflammatory Therapy in Osteoarthritis of the Knee Joint

Abstract: Eighty-nine patients with established OA of the knee joint, already on regular NSAIDs for joint pain, were randomly allocated to receive 100 mg/day of slow release diclofenac (45 patients) or matching placebo (44), in place of their NSAID, for 2 years. Thirty-eight patients withdrew or dropped out of the study. The major causes for withdrawal were lack of efficacy (three active, 12 placebo, P < 0.01) or side effects (six active, five placebo), and most withdrawals occurred within the first 6 months. Long term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(42 citation statements)
references
References 0 publications
3
36
1
2
Order By: Relevance
“…As the radiographic assessment, which was conducted independently by 5 investigators, did not find structural improvement in the treated joints, it appears that the improved scores in force-plate, orthopedic, and owner's assessments were due to ADSC's anti-inflammatory and/or immunomodulatory effects. Similar negative radiographic findings in OA patients treated with NSAIDs have been reported previously [22] . The present study is also similar to the three aforementioned veterinarian studies in that the presence of the injected ADSCs in the treated joint could not be confirmed due to the fact that these patients are companion dogs, not experimental canine models, and as…”
supporting
confidence: 89%
“…As the radiographic assessment, which was conducted independently by 5 investigators, did not find structural improvement in the treated joints, it appears that the improved scores in force-plate, orthopedic, and owner's assessments were due to ADSC's anti-inflammatory and/or immunomodulatory effects. Similar negative radiographic findings in OA patients treated with NSAIDs have been reported previously [22] . The present study is also similar to the three aforementioned veterinarian studies in that the presence of the injected ADSCs in the treated joint could not be confirmed due to the fact that these patients are companion dogs, not experimental canine models, and as…”
supporting
confidence: 89%
“…Non-steroidal anti-inflammatory drugs (NSAIDs) and opiates are the main drugs that are commonly prescribed to OA patients, but they only provide symptomatic relief [70,71]. It is thus envisioned that a new generation of drugs could fill this gap and significantly slow down the disease process, as well as providing symptomatic relief, addressing the dual need for symptom and structure modification.…”
Section: Clinical Trials For Arthritic Diseasesmentioning
confidence: 99%
“…When medical therapies have failed and the patient has an unacceptable reduction in their quality of life and ongoing pain and disability, then at least for knee and hip OA, total joint arthroplasty is indicated. Intrarticular (IA) corticosteroid injections have been used for decades in clinical practice for pain relief and control of local inflammation in OA (Dieppe et al, 1993). Intrarticular corticosteroid injections are part of the treatment paradigm suggested in the American College of Rheumatology (ACR) practice for the treatment of knee OA 34 .…”
Section: Intra-articular Injectionsmentioning
confidence: 99%